Adenovirus vector and mRNA vaccines: mechanisms regulating their immunogenicity - Provine, NM; Klenerman, P (Wiley, 2022)
Replication-incompetent adenovirus (Ad) vector and mRNA-lipid nanoparticle (LNP) constructs represent two modular vaccine platforms that have attracted substantial interest over the past two decades. Due to the COVID-19 pandemic and the rapid development of multiple successful vaccines based on these technologies, there is now clear real-world evidence of the utility and efficacy of these platforms. Considerable optimization and refinement efforts underpin the successful application of these technologies. Despite this, our understanding of the specific pathways and processes engaged by these vaccines to stimulate the immune response remains incomplete. This review will synthesize our current knowledge of the specific mechanisms by which CD8+ T cell and antibody responses are induced by each of these vaccine platforms, and how this can be impacted by specific vaccine construction techniques. Key gaps in our knowledge are also highlighted, which can hopefully focus future studies.